The Effect of the Empowerment Program on the Chronic Sorrow of the Parents of Premature Newborn in Neonatal Intensive Care Units - H Moradi; L Borimnejad; N Seyed Fatemi; H Haghani; M Moradi (Iran University of Medical Sciences, 2019)
Background & Aims: Sorrow is a natural response to events such as the loss of premature or abnormal neonates, which if prolonged, increases the risk of chronic physical illnesses. The main task of nurses to alleviate the pain of the parents whose infants are admitted to the neonatal intensive care unit (NICU) is to empower them for the care of the premature infants. The present study aimed to assess the effects of the empowerment program on the chronic sorrow of the parents of the premature neonates admitted to the NICU. Materials & Methods: This non-randomized clinical trial was conducted with a control group on 68 parents with premature infants admitted to the NICUs of Rasoul Akram and Ali Asghar hospitals in Tehran, Iran. The subjects were selected via convenience sampling, and their stratification into two groups of intervention and control was based on a time framework. Data were collected using a demographic questionnaire and Kendall chronic sorrow instrument in both groups, and the intervention group received the empowerment program. The training was performed in groups of 2-4 of the parents, and one month after the intervention, Kendall chronic sorrow instrument was completed by the subjects again online. Data analysis was performed in SPSS version 16 using descriptive and inferential statistics. Results: No significant differences were observed between the intervention and control groups in terms of the demographic characteristics (P>0.05). Before the intervention, the mean score of parental chronic sorrow had no significant difference in the study groups (P>0.05). After the intervention, the mean score in the control and intervention groups was 43.11±8.38 and 32.85±5.45, respectively, which indicated a significant difference in this regard (P<0.001) and the effectiveness of the empowerment program in decreasing the chronic sorrow of the parents of the premature infants admitted to the NICU. Conclusion: According to the results, the empowerment program was effective in the reduction of the chronic sorrow of the parents of the premature infants admitted to the NICU. Therefore, it is recommended that this program be used as an effective and cost-efficient strategy in NICUs.